Children’s perspectives on occupational participation in UK primary schools - Jamie Liddell; Tara Sims; Clare Sugarman-Clarke (British Journal of Occupational Therapy, 2026)
Introduction: Occupational participation is a fundamental right for all children, yet little is known about how UK primary-aged children experience it in school. This study explored their views on meaningful occupations, school demands, and factors influencing participation. Method: Eleven children aged 7–11 from three UK mainstream primary schools participated in the first phase of a Critical Participatory Action Research study. Data were collected through photo tours and discussion groups and analysed using reflexive thematic analysis. The Canadian Model of Occupational Participation (CanMOP) guided interpretation. Findings: Five themes emerged: (1) Environment, (2) Rules and Fairness, (3) Friendship, (4) Learning, and (5) Power of the Teacher. Children valued comfort, autonomy, emotional safety, and relationships. Participation was shaped by rules, sensory environments, peer dynamics, and teacher behaviours. Canadian Model of Occupational Participation highlighted influences across micro, meso, and macro levels. Conclusion: Listening to children’s voices is essential for creating inclusive school environments. Occupational therapists can promote participation through universal, tiered, and collaborative approaches that address individual and systemic barriers.